Comparative study between aperture and suspensary fixation of hamstring autografts on femoral side in ACL reconstruction: clinical and radiological outcome assessment - R. Kashid, Manoj; S., Rahool; Chaudhry, Amit; ., Rajshekhar; Singh, Varunendra Bahadur; Bhaskarwar, Ajit (International Journal of Research in Orthopaedics, 2017)
Background: Arthroscopically aided anterior cruciate ligament reconstruction using hamstring graft can be fixed to femoral condyle by suspensory and aperture fixation methods. The following study was undertaken to investigate whether there is any difference in functional outcomes with these fixation methods as measured by the Lysholm knee score and to determine tunnel widening post operatively with these two methods and does it affect the functional outcome. Methods: 50 patients of clinically and radiologic ally diagnosed ACL tear fulfilling the inclusion and exclusion criteria were randomized into two groups to undergo arthroscopic ACL reconstruction using quadrupled hamstring graft with suspensory (n=25) and aperture (n=25) fixation methods on femoral side. They were compared post operatively with Lysholm score, clinical laxity tests and percentage of tunnel enlargement using computed tomograms at 01 year. Results: At the end of 6 months there was no much difference in Lysholm score between both the groups (P =0.663) and at the end of 01 year aperture group had slightly better outcome. However, the difference was not statistically significant (p =0.173). There was more tunnel widening in the suspensory group especially of the femoral tunnel in the coronal plane. However, the amount of tunnel widening in both the groups was not significant statistically (P =0.071 and P =0.963). Tunnel widening is not associated with inferior clinical outcomes or functional knee score. Conclusions: Aperture and Suspensory fixation methods of hamstring graft at femoral condyle in ACL reconstruction are comparable clinically and there is no advantage of one particular method over other. Although comparatively more tunnel widening is seen in suspensory fixation methods; it does not affect the final clinical outcomes or functional knee scores.